THE CONCEPT OF COMMUNICATIVE COMPETENCE AND ITS IMPORTANCE IN SCHOOL MANAGEMENT (International journal of artificial intelligence, 2025)
This article analyzes the theoretical content of the concept of communicative competence and its role in modern school management. It also highlights the necessity of developing communicative competence in the context of digital transformation. The results of the study show that communicative competence serves as a crucial factor in improving the effectiveness of school management.